Abundance of Fe(III) during cultivation affects the microbiologically influenced corrosion (MIC) behaviour of iron reducing bacteria Shewanella putrefaciens. (September 2020) - Wurzler, Nina; Schutter, Jan David; Wagner, Ralph; Dimper, Matthias; Lützenkirchen-Hecht, Dirk; Ozcan, Ozlem
Graphical abstract: Highlights: Application of grazing incidence XANES to microbially influenced corrosion (MIC). Reflectivity data contains information on the changes of the oxide layer thickness. In situ electrochemical XANES allows the analysis of the biofilm-metal interface. Shewanella spp. grown in abundance of Fe(III) show higher electrochemical activity. Oxide growth during MIC leads to inhibition of localized (pitting) corrosion. Abstract: The effect of the presence of Fe(III) during the cultivation on the electrochemical activity and corrosion behaviour of dissimilatory iron reducing bacteria Shewanella putrefaciens was studied by means of ex situ and in situ X-ray absorption near-edge spectroscopy (XANES). Stainless steel AISI 304 and thin iron films were studied as substrates. XANES analysis indicated an accelerated iron dissolution and growth of an oxide/hydroxide film for the culture grown with Fe(III) in comparison to the culture grown in absence of Fe(III). Electrochemical analysis indicated that the biofilm resulted in acceleration of the general corrosion but provides protection against local corrosion.